Learn algorithmic trading : build and deploy algorithmic trading systems and strategies using Python and advanced data analysis /: build and deploy algorithmic trading systems and strategies using Python and advanced data analysis. (2019) - Donadio, Sebastien; Ghosh, Sourav
No abstract available